A presença dos Museus da Imagem e do Som na web - Isac Daniel Santana (2022)
This dissertation aims to understand how the Museums of Image and Sound (MISes) are implementing and managing their presence on the Web, highlighting the actions of dissemination of digital audiovisual collections. We undertake reflections on memory and the Brazilian audiovisual heritage, as well as the impact that the digital revolution has caused in museums with this typology. Within this scenario, we aimed to identify the relationship between MISes and online environments, evaluating the diffusion of digitalized and native digital collections through their own platforms, such as websites, or commercial ones, such as social networks. The methodological resources were bibliographic review, active data collection, and online questionnaires. The results point to less structured uses of dissemination of this collection, focusing more on social networks and less on resources whose information retrieval is more professional and effective, such as digital repositories. The online actions were diversified, ranging from web radio to virtual tours. We hope that this work can serve as a decision-making subsidy for professionals in the museum field, both through the gaps it identifies and the good practices it highlights, which can serve as inspiration in the management and preservation of our precious Brazilian audiovisual heritage.